Accounting for Growth in Latin America and the Caribbean : Improving Corporate Financial Reporting to Support Regional Economic Development - Fortin, Henri; Hirata Barros, Ana Cristina; Cutler, Kit (Washington, DC: World Bank, 2013)
In the Latin America and Caribbean (LAC) region, as in the rest of the world, reliable financial information is the cornerstone of a robust market economy and efficient public sector. This book presents both an analysis of the broader trends derived from the individual country-level studies produced under the Report on the Observance of Standards and Codes (ROSC) Accounting and Auditing (A&A) program and a synthesis of lessons learned from the Bank's experiences working with policy makers and other stakeholders to implement the ROSC A&A recommendations. This first chapter introduces the book by showing how sound A&A practices in the private and public sectors contribute to LAC development agenda, and by describing the regional economic context. It then presents three case studies of successful financial reporting and auditing reforms within LAC, showing how these reforms have benefited the countries. It describes drivers of reform that have led some countries to adopt global standards of good A&A practice and others to take a more conservative, wait and see approach. Finally, the chapter describes the objectives and methodology of this study, and the structure of the book.